Erytropoetyna, białko von Hippel-Lindau i rak nerki: molekularne podstawy towarzyszącego chorobie nowotworowej zespołu erytrocytozy - J. Sytkowski, Arthur (Contemporary Oncology/Współczesna Onkologia, 2005)
Erythropoietin (Epo) is a glycoprotein hormone that is the principal regulator of red blood cell production. In the adult, it is produced primarily in the kidney in response to hypoxia or reduced hemoglobin. Hypoxic regulation of Epo production is due to activation of the Epo gene by HIF-1 (hypoxia inducible factor-1), a heterodimeric transcription factor comprising HIF-1 a and HIF-1 β subunits. In the presence of oxygen, the HIF-1 α subunit is rapidly proteolysed by a mechanism involving hydroxylation of specific prolyl residues and interaction with von Hippel-Lindau protein (pVHL). In reduced oxygen, HIF-1 α is stabilized, resulting in enhanced gene transcription. The Epo gene is but one of numerous genes, such as the pro-angiogenic VEGF, that are regulated in this manner. The inherited cancer syndrome von Hippel-Lindau disease is characterized by a mutated VHL gene leading to the absence of hypoxic gene regulation. The result is the constitutive expression of normally hypoxically regulated genes, including Epo. Some cases of renal cysts and renal cancer are caused by somatic mutations of the VHL gene in the renal tissue, and these cases often exhibit increased Epo production and the paraneoplastic syndrome of erythrocytosis. Those renal cancers resulting from other mutations but possessing normal VHL genes do not produce Epo. Also, there is heterogeneity of VHL gene deletions within individual renal cell carcinoma tumors, leading to a more complex clinical picture.